Why Underachievers Dominate Secret Police Organizations: Evidence from Autocratic Argentina. Issue 4 (26th September 2019) - Scharpf, Adam; Gläßel, Christian
Abstract: Autocrats depend on a capable secret police. Anecdotal evidence, however, often characterizes agents as surprisingly mediocre in skill and intellect. To explain this puzzle, this article focuses on the career incentives underachieving individuals face in the regular security apparatus. Low‐performing officials in hierarchical organizations have little chance of being promoted or filling lucrative positions. To salvage their careers, these officials are willing to undertake burdensome secret police work. Using data on all 4, 287 officers who served in autocratic Argentina (1975–83), we study biographic differences between secret police agents and the entire recruitment pool. We find that low‐achieving officers were stuck within the regime hierarchy, threatened with discharge, and thus more likely to join the secret police for future benefits. The study demonstrates how state bureaucracies breed mundane career concerns that produce willing enforcers and cement violent regimes. This has implications for the understanding of autocratic consolidation and democratic breakdown.